Comparison of Public Sector Efficiency Levels in the Economies of the 10 Largest Provinces in Indonesia - Sari, Aprilia Herlina; Wasil, Mohammad (East Asian Journal of Multidisciplinary Research, 2024)
Efficiency in the public sector not only affects economic growth but also affects productivity in each province. The efficiency of public sector operations plays an important role in driving economic growth and development. This study examines the differences in public sector efficiency in 10 provinces with the highest economies in Indonesia. A total of 10 provinces with observation years 2019–2023 were the samples of this study. This study uses the Data Envelopment Analysis (DEA) method. The data used comes from the Central Statistics Agency (BPS). The research findings show that inefficiency in each province occurs because the input sector used is larger than the output sector, so that public sector operations are not optimal.